Regulating algorithmic care in the European Union: evolving doctor–patient models through the Artificial Intelligence Act (AI-Act) and the liability directives - Barry Solaiman (19160614) (2024)
This article argues that the integration of artificial intelligence (AI) into healthcare, particularly under the European Union’s Artificial Intelligence Act (AI-Act), poses significant implications for the doctor–patient relationship. While historically paternalistic, Western medicine now emphasises patient autonomy within a consumeristic paradigm, aided by technological advancements. However, hospitals worldwide are adopting AI more rapidly than before, potentially reshaping patient care dynamics. Three potential pathways emerge: enhanced patient autonomy, increased doctor control via AI, or disempowerment of both parties as decision-making shifts to private entities. This article contends that without addressing flaws in the AI-Act’s risk-based approach, private entities could be empowered at the expense of patient autonomy. While proposed directives like the AI Liability Directive (AILD) and the revised Directive on Liability for Defective Products (revised PLD) aim to mitigate risks, they may not address the limitations of the AI-Act. Caution must be exercised in the future interpretation of the emerging regulatory architecture to protect patient autonomy and to preserve the central role of healthcare professionals in the care of their patients. Other Information Published in: Medical Law Review License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/medlaw/fwae033